A cross-sectional study to evaluate smartphone addiction among undergraduate medical students - Pomal, Parth; Khilnani, Ajeet Kumar; Gala, Vibhuti (International Journal of Research in Medical Sciences, 2026)
Background: The rapid global proliferation of smartphones has raised concerns regarding “smartphone addiction,” a behavioural condition characterized by compulsive use and functional impairment. Medical students, due to high academic demands and extensive reliance on digital platforms, may be particularly vulnerable. This study aimed to estimate the prevalence of smartphone addiction among undergraduate medical students in Kutch, Gujarat, India and to examine factors associated with addictive smartphone use. Methods: A cross-sectional study was conducted among 195 undergraduate medical students between April 2025 and June 2025. Data were collected using a pre-designed, pre-tested structured questionnaire that included the Smartphone Addiction Scale–Short Version (SAS-SV). Smartphone addiction was determined using the established cut-off score of ≥ 33. Associations between smartphone addiction and demographic or usage-related variables were evaluated using the Chi-square test. Results: Among the 195 participants, 51 students met criteria for smartphone addiction, yielding a prevalence of 26 percent. Participation was highest from Phase-3 Part-2 (n=58), with 11 identified as addicted, while Phase-1 showed the highest number of addicted students (n=20 out of 57). Most respondents reported average daily smartphone use of 3–6 hours (n=91), with 28 classified as addicted. Social media was the most common primary use (n=98), among whom 33 were addicted. Academic phase, daily duration of use and primary purpose of use did not show statistically significant associations with smartphone addiction. In contrast, students’ self-perception of smartphone use demonstrated a highly significant association (p<0.00001). Conclusions: Self-perception of excessive smartphone use emerged as the only significant predictor of smartphone addiction, underscoring the importance of subjective awareness when designing preventive or corrective strategies for medical students.